Colombian traditional music and its basic structures: afro- colombian music (part i) (2005)
The main objective of this article is to introduce the basicelements of the musical structures of traditional Colombianmusic of African origin. It is divided in two sections.The first one is dedicated to a brief historical review ofits research tradition and of the methodological andanalytical framework of the study. In the second one themusical structures will be discussed in the Colombianand Afro-Latin American contexts. Moreover, this textis part of a larger project which eventually will deal withother Colombian musical styles as documented duringthe last quarter of the 20th century.